Perceived discrimination is associated with health behaviours among African-Americans in the Jackson Heart Study. Issue 2 (28th September 2015) - Sims, Mario; Diez-Roux, Ana V; Gebreab, Samson Y; Brenner, Allison; Dubbert, Patricia; Wyatt, Sharon; Bruce, Marino; Hickson, DeMarc; Payne, Tom; Taylor, Herman
Abstract : Background: Using Jackson Heart Study data, we examined associations of multiple measures of perceived discrimination with health behaviours among African-Americans (AA). Methods: The cross-sectional associations of everyday, lifetime and burden of discrimination with odds of smoking and mean differences in physical activity, dietary fat and sleep were examined among 4925 participants aged 35–84 years after adjustment for age and socioeconomic status (SES). Results: Men reported slightly higher levels of everyday and lifetime discrimination than women and similar levels of burden of discrimination as women. After adjustment for age and SES, everyday discrimination was associated with more smoking and a greater percentage of dietary fat in men and women (OR for smoking: 1.13, 95% CI 1.00 to 1.28 and 1.19, 95% CI 1.05 to 1.34; mean difference in dietary fat: 0.37, p<0.05 and 0.43, p<0.01, in men and women, respectively). Everyday and lifetime discrimination were associated with fewer hours of sleep in men and women (mean difference for everyday discrimination: −0.08, p<0.05 and −0.18, p<0.001, respectively; and mean difference for lifetime discrimination: −0.08, p<0.05 and −0.24, p<0.001, respectively). Burden of discrimination was associated with more smoking and fewer hours of sleep in women only. Conclusions: Higher levels of perceived discrimination were associated with select health behaviours among men and women. Health behaviours offer a potential mechanism through which perceived discrimination affects health in AA.